'Sur' Realism: After Surrealism Comes Hyperrealism. (1st March 2018) - Alonso, Hernan Diaz
Abstract : If Surrealism was originally about freeing the subconscious, what is its relevance in our now‐liberated era? Despite avowed sympathies with the Surrealist movement, Hernan Diaz Alonso – Principal of Los Angeles‐based architectural practice Xefirotarch and Director and CEO of the Southern California Institute of Architecture (SCI‐Arc) – argues that the way forward for visionary architecture in the digital age lies instead in the creation of new coherencies: a hyperrealism of the present that exploits and transforms clichés.